Financing, adjustment, and the International Monetary Fund - Kenen, Peter B. (Washington, D.C. : Brookings Institution, 1986)
In this study, the author examines the evolution of the Fund as a financial institution and argues that the modifications made in the last decade have altered the fundamental character of the institution
osc 28/10/2019
Loans
Keywords: International Finance; International Monetary Fund